Victorian trabeculectomy audit. (26th April 2017) - Fan Gaskin, Jennifer C; Sandhu, Sukhpal S; Walland, Mark J
Abstract: Importance: This study highlights the efficacy and safety of trabeculectomy in Victoria, Australia. Background: Trabeculectomy is currently the gold standard in glaucoma surgery. However, its role has been increasingly questioned because of its associated risks and complications. This audit aimed to assess the efficacy and safety of trabeculectomy surgery in the state of Victoria, Australia. Design: A cross‐sectional, retrospective and voluntary statewide audit of trabeculectomy surgery by individual surgeons in 2012 with 24 months follow‐up. Participants: Twenty‐four surgeons in the state of Victoria submitted data on 227 trabeculectomies. Methods: Basic preoperative and perioperative data were collected. Post‐operative data collected included intra‐ocular pressure measurements, glaucoma medications, associated complications and subsequent surgery up to 24 months post‐trabeculectomy. Main Outcome Measures: The main outcome measures were post‐operative intra‐ocular pressure and surgical complications. Results: At 12 months, the mean intra‐ocular pressure was 12.6 ± 4.1 mmHg (range 3–28 mmHg). A total of 91% of eyes had an intra‐ocular pressure ≤18 mmHg with or without ocular hypotensive medications. One‐third of eyes that were phakic at the time of trabeculectomy underwent cataract extraction within the 24 months of follow‐up. Eyes that underwent combined cataract extraction and trabeculectomy (23% of trabeculectomies) had a significantly higher mean 12‐month intra‐ocular pressure than eyes that underwent trabeculectomy alone (13.9 vs . 12.2 mmHg, P = 0.01). At 24 months, there were no cases of blebitis/endophthalmitis. Conclusions and Relevance: The Victorian Trabeculectomy Audit demonstrates excellent efficacy and safety results that are comparable with international standards. Combined cataract extraction and trabeculectomy tended to result in a higher mean post‐operative intra‐ocular pressure than trabeculectomy alone.